Possible Decision Rules to Allocate Quotas and Reservations to Ensure Equity for Nepalese Poor - Shakya, Shishir; Lama, Nabraj (Economic Journal of Development Issues, 2016)
Government of Nepal provides quotas and reservations for women, indigenous nationalities, Madhesi, untouchables, disables and people of backward areas. These statuses are not homogenous in economic sense. We proposed few other decision trees (rules) that can predict household poverty in Nepal based on 14,907 household observations employing classification and regression tree (CART) approach. These decision rules were based on few practically answerable questions (for respondents) and can be cross checked easily by the enumerators. We modeled 5 different scenarios that respondents were likely to answer the asked questions. These decision rules were 94% to in worst-case scenario 70% accurate in out-of-sample dataset. These proposed meaningful decision rules can be helpful on policy making and implementation that relate to positively discriminate (quota and reservation) for those who lie below poverty line. Economic Journal of Development Issues Vol. 17 & 18 No. 1-2 (2014) Combined Issue, Page: 149-162 This research was completed when both authors were pursuing Masters of Arts in Economics in Patan Multiple Campus, Tribhuvan University